Electrical Appliance Ownership and Usage in Ireland - LEAHY, EIMEAR; LYONS, SEAN; WALSH, SHARON (ESRI)
Past research into the determinants of appliance ownership has identified associations with socioeconomic characteristics of households. Few studies have examined the intensity with which different sorts of households use the appliances they have. This paper uses microdata to examine the factors influencing ownership and usage of electrical appliances in Irish households. We also consider the factors influencing the ownership of different cooker types, space and water heating systems and energy saving features. We find that appliance ownership and usage is related to the socio-economic characteristics of the household's chief income earner as well as household characteristics such as the type and age of accommodation, tenure and the number of bedrooms. The number of people living in the household has a positive association with both ownership and usage of electrical appliances. However, it does not increase ownership of energy saving features, with the exception of CFLs. The highest earning households are more likely to own electrical appliances but they do not necessarily use them more often, nor are they more likely to purchase energy saving features.
PUBLISHED
Keywords: Electrical appliance ownership; Appliance usage; Energy saving features